CORRELATION OF EFFECTIVE INERTIA OF CASTELLATED BEAMS WITH SPAN-TO-DEPTH RATIO - Sutedjo Krisnadi; Ignatius Sudarsono; Rully Savitri Nurvita; Nadiv Raka Pradifa (LPPM Universitas Negeri Jakarta, 2026)
Material efficiency in structural systems can be enhanced through cross-sectional optimization of structural elements, one of which is the use of castellated steel beams. A castellated beam has an increased section depth without adding material volume from the original beam. Although several studies have investigated the flexural performance of castellated beams, analytical studies on the moment of inertia, particularly those considering the effect of shear deformation, remain limited. This study compares the net moment of inertia (Inett) based on the AISC Design Guide 31 with the effective moment of inertia (Ieff) obtained from Finite Element Analysis (FEA). Beam models were developed with total depths (dg) ranging from 450 mm to 1350 mm and span lengths (L) from 6000 mm to 18000 mm. The Ieff values were derived from the midspan deflection under uniformly distributed loading and correlated with the L/dg ratio. Results show that Ieff increases with the increasing L/dg and tends to converge. Empirical correlation between L/dg and Inett/Ieff was obtained with a coefficient of determination of R2 = 0.9412. When L/dg ≥ 18, the Inett/Ieff ratio is less than 1.1, indicating that the difference between Inett and Ieff is below 10%. Therefore, the Inett can be safely used for structural design. The findings provide a practical guideline for estimating the effective flexural stiffness of castellated beams and contribute to the development of analytical and numerical approaches for their structural design.